Factors Influencing Financial Sustainability of Microfinanc Institution in Kenya - Mbithi, Maluki Mark (University of Embu, 2020)
Giving poor the entree of financial facilities as a means of eradicating poverty in past decade has gain fame. This resulted after emergence of model that have revealed increasing victory in term of capability to reach poor and nourishing the financial provision delivery. Though a number of microfinance remain to struggle. This study seek to found factors swaying financial sustainability of microfinance organizations in operating in Kenya. The reason of research is to increase better understanding of the features which are significant for microfinance sustainability in Kenya. Approach used in include a descriptive design, study in search of to explore the status quo of microfinance organization in Kenya. The study used secondary data from 15 microfinance institutions. The data acquired was evaluated by means of deceptive statistics. From the study, the researcher establish that financial regulation, number of clients served and geographical coverage and outreach remained the issues that stimulus financial sustainability of microfinance organization highly. The study henceforth established sustainability of microfinance organization is a function of countless features that are linked and inter connected. Scholar concluded too mandatory saving stays a sector to microfinance organization financial sustainability. The study endorse that many extra branch ought to be opened toward reaching many customers as possible which resolve improve sustainability aimed at them to last well and safeguard them observe to rule and regulation of registration and government policies.